Non Formal Primary Education (NFPE) II 1996-1999: final evaluation, 25th July-11th August 1999 - Ryan, Anne; Taylor, Barry (© BRAC, 2016)
1. Introduction 2. Quantitative analysis of achievements in phase II: Review of NFPE against the logical framework, Cost efficiency and effectiveness of NFPE schools, NFPE management 3. Qualitative analysis of achievements in phase II: Quality improvements introduced in phase II, Pilot school activities 4. The future: Implications for NFPE phase III 5. Conclusion.